Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmed.2022.981405
|View full text |Cite
|
Sign up to set email alerts
|

Association between cervical disorders and adverse obstetric outcomes: A retrospective cohort study

Abstract: ObjectiveThe purpose of this study was to explore the association of cervical disorders on obstetric outcomes of singleton pregnancies in China.MethodsThis hospital-based retrospective cohort study of women with live singleton births included 71,097 Chinese women. We compared the risk of adverse obstetric outcomes in different types of pregnancies with cervical disorders with those with normal cervix. Logistic regression model was used to estimate the association between cervical disorders and adverse obstetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The finding that abortions were more prevalent after CIN treatment is similar to that of Sun et al, 2022& Weinmann et al, 2017 that observed an association between pregnancy loss and ablative surgical treatment and suggested further investigation. Similarly, the finding that low birth weight was a significant adverse outcome aligns with previous studies examining the impact of CIN treatment on pregnancy outcomes [21] [22].…”
Section: Discussionmentioning
confidence: 66%
“…The finding that abortions were more prevalent after CIN treatment is similar to that of Sun et al, 2022& Weinmann et al, 2017 that observed an association between pregnancy loss and ablative surgical treatment and suggested further investigation. Similarly, the finding that low birth weight was a significant adverse outcome aligns with previous studies examining the impact of CIN treatment on pregnancy outcomes [21] [22].…”
Section: Discussionmentioning
confidence: 66%